EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING BERBANTUAN MEDIA LEAFLET TERHADAP HASIL BELAJAR SISWA SMA NEGERI MATAWAI LA PAWU - Roslinda Tamu Apu; Anita Tamu Ina; Yohana Ndjoeroemana (Jurnal Genta Mulia, 2025)
This research is motivated by low student learning outcomes, lack of learning resources, and learning media used in the classroom are not varied. So that it causes students' responses to be less active in the learning process in the classroom. The purpose of this study was to determine whether or not there was an influence of the snowball throwing type cooperative learning model assisted by leaflet media on student learning outcomes at SMA Negeri Matawai La Pawu. This study uses a quantitative approach. Experimental class, and X Ipa-1 as the experimental class and X Ipa-2 as the control class. Tests were conducted to collect data. Validity and reliability tests, descriptive analysis, normality and homogeneity tests and sample and independent sample hypothesis tests were all conducted using SPSS. The average post-test value for the experimental class was 77.43 while the average post-test value for the control class was 69. Hypothesis testing conducted showed a significant effect indicated by the Asymp Sig (2-tailed) value of 0.001, which means less than 0.05. Thus, the use of the snowball throwing type cooperative learning model assisted by leaflet media has an impact on the learning outcomes of class X-Ipa 1 students at Matawai La Pawu State Senior High School.